PALAEOCLIMATOLOGY AND PALAEOHYDROLOGY OF LATE PLEISTOCENE PALAEOLAKE AT QA'A SELMA (JORDANIAN BADIA) - Al-Tawash, Balsam; Al-Qudah, Khaldoun (Iraqi Journal of Science, 2024)
Qa'a Selma (as a playa) is located on the northern basaltic flow of northeast Jordan, about 35 km northeast of the Safawi town. The present climate of the region is characterized by seasonal rain (during winter) and it has mild winter and temperate dry summer. Late Pleistocene palaeoclimatic and palaeohydrologic conditions of Qa'a Selma are deduced based on lake level changes. One palaeoshoreline was delineated at 745m a.s.l. and 4m above the present one (1m above the bottom of Qa'a). The Qa'a is located at 740m a.s.l. The present Qa'a area is calculated to equal 18 km2, where its area has increased during the Late Pleistocene pluvial period and calculated to reach 36 km2. The Drainage basin area is calculated as well to equal 15000 km2.The present hydrological balance is calculated. The present potential evaporation PE and actual evaporation AE over the catchment area are calculated to equal 835 mm/ year and 69.01 mm/ year respectively.Free surface evaporation from the lake surface is calculated to be 1643 mm/ year. Two climatic models are proposed, with the assumed mean annual palaeotemperature 4°C and 8°C less than present one (18.9°C), for the first and second climatic models respectively.For the first climatic model (mean annual palaeotemperature is 14.9°C, 4°C less than present and mean annual palaeoprecipitation 450 mm/ year, ~380mm greater than present), the potential evapotranspiration and the actual evaporation are calculated to be 816 mm/ year and 436 mm/ year respectively.The free surface evaporation from the lake surface EL is calculated to equal 1392.6 mm/ year. The palaeorunoff under these condition is calculated as well to equal 14mm/ year, as water volumes required to form and maintain the palaeolake, equal to 210 x106 m3/ year.Whereas under the proposed climatic conditions of the second model (mean annual palaeotemprature equal to 10.9°C, 8°C less than present and mean annual palaeoprecipitation 380mm/ year, or 310 mm/ year greater than presents).Potential evapotranspiration and the actual evaporation are calculated, as 658 mm/year and 368 mm/ year respectively. The free surface evaporation EL is calculated as well, and equal 1111mm/ year. The Estimated palaeorunoff is 12mm/ year and as volume of water equal to 180x 106 m3/ year. This amount of water that is needed to form and maintain the palaeolake at the Qa'a area.So that most probably climatic conditions similar to those of the first and second models might prevailed in the northeast Jordanian Badin throughout Late Pleistocene pluvial periods (37-32 ka BP) and (15.5-13.9 ka BP), which led to form and maintain the palaeolake at the Qa'a area.